Study ofVarious Insulation Materials onthe performance of Non-Convecting Solar Pond in Malaysia - Ismail, Mohamad Rizal (Universiti Teknologi Petronas, 2004)
The study will focus on the types of insulation that will be used in order to maintain the temperature of salty concentration. This can be detected from the calculation of heat loss (Qioss). The less heat loss calculated, the better the insulator could be. However, in order to find the heat loss, one must determine the amount of solar radiation absorbed by the sun via radiation. To measure the total radiation that had been produced by the sunlight, photo radiometer or solarimeter had been used as the main device. Besides that, thermometer is used to measure the temperature of the surrounding and the temperature ofthe polystyrene. The solar pond is using the salinity gradient solar technology. The purpose of solar pond is to collect and store solar energy. For this project, the writer has decided that the solar pond should have the depth of 2 inches of brine while the remaining 3 inches (5 inches total in depth) is the salinity gradient part (Non Convective Zone and Upper Convective Zone). 3 materials had been suggested for this project, which is polystyrene, polyurethane and cardboard paper. Whilst the first two has been regarded as the insulation materials, the final one is not. However, in order to test the hypothesis (theory) with the actual experiment, such condition is chosen before completing the project. Finally, the project should be a useful addition in order to understand the concept ofthe salinity gradient solar pond and its insulator. This is because; it applied the heat transfer concept of conduction and convection. Hence, the outcome of this project should give benefits for all ofthe persons involved; particularly the student himself.